Leadership in technical operations: bridging engineering solutions and business support - Vadym Lolin (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
This paper analyses leadership in technical processes and study of how organizational engineering addresses the transition between operational technical solutions and business enablers. The paper focuses on one data set of 10 leading companies across industries for the period, 2019 to 2023, which explores the resultant impact of the engineering practice employed in technical operations on operation efficiency, resources utilization, and business performance. The study implies that leadership that is efficient in technical processes enhances organizational gains by promoting innovation, balancing resource utilization and increasing system dependability. The organisations that adopt technical strategy, where the engineering functions are aimed at supporting business goals, report enhanced processes in decision making and flexibility relative to the emergence of new technologies. It also reveals that successful adoption of sustainable manufacturing strategies requires cross-functional co-ordination and a culture that encourages constant organizational improvement for long-term incremental competitive advantage. The research presents ideas which can be implemented for organizations that want to use the engineering processes to improve the organizational workflow, with a focus on activities for integrating technical procedures into the organizational strategies.